Tailoring re-entrant geometry in inverse colloidal monolayers to control surface wettability - Utech, Stefanie; Bley, Karina; Aizenberg, Joanna; Vogel, Nicolas (Journal of Materials Chemistry A, 2016)
Controlling the microscopic wetting state of a liquid in contact with a structured surface is the basis for the design of liquid repellent as well as anti-fogging coatings by preventing or enabling a given liquid to infiltrate the surface structures. Similarly, a liquid can be confined to designated surface areas by locally controlling the wetting state, with applications ranging from liquid transport on a surface to creating tailored microenvironments for cell culture or chemical synthesis. The control of the wetting of a low-surface-tension liquid is substantially more difficult compared to water and requires surface structures with overhanging features, known as re-entrant geometries. Here, we use colloidal self-assembly and templating to create two-dimensional nanopore arrays with tailored re-entrant geometry. These pore arrays, termed inverse monolayers, are prepared by backfilling a sacrificial colloidal monolayer with a silica sol-gel precursor material. Varying the precursor concentration enables us to control the degree to which the colloids are embedded into the silica matrix. Upon calcination, nanopores with different opening angles result. The pore opening angle directly correlates with the re-entrant curvature of the surface nanostructures and can be used to control the macroscopic wetting behavior of a liquid sitting on the surface structures. We characterize the wetting of various liquids by static and dynamic contact angles and find correlation between the experimental results and theoretical predictions of the wetting state based on simple geometric considerations. We demonstrate the creation of omniphobic surface coatings that support Cassie–Baxter wetting states for liquids with low surface tensions, including octane ( extgreekg = 21.7 mN m-1). We further use photolithography to spatially confine such low-surface-tension liquids to desired areas of the substrate with high accuracy.